Identification and characterization of sporulation gene spoVS from Bacillus subtilis. - Resnekov, O (1995)
We report the identification and characterization of an additional sporulation gene from Bacillus subtilis called spoVS, which is induced early in sporulation under the control of sigma H. We show that spoVS is an 86-codon-long open reading frame and is capable of encoding a protein of 8,796 Da which exhibits little similarity to other proteins in the databases. Null mutations in spoVS have two contrasting phenotypes. In otherwise wild-type cells they block sporulation at stage V, impairing the development of heat resistance and coat assembly. However, the presence of a spoVS mutation in a spoIIB spoVG double mutant (which is blocked at the stage [II] of polar septation) acts as a partial suppressor, allowing sporulation to advance to a late stage. The implications of the contrasting phenotypes are discussed in the context of the formation and maturation of the polar septum.